Pengaruh Promosi dan Harga Terhadap Minat Beli di Pusat Grosir PIK (PGP) Jakarta Timur - Safriadi M Yunus Aks (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This study aims to determine the effect of promotion and price on people's buying interest at PGP PIK Mall, Penggilingan, Cakung, East Jakarta. The sample used in this study was 100 respondents. The method in this study used Random Sampling Technique, using a questionnaire, Data analysis using the SPSS Version 25 Program. The data analysis methods used were regression analysis, multiple correlation, coefficient of determination, hypothesis testing using the t test and f test. Based on the results of the study, it can be concluded that both promotion and price have a significant influence on people's buying interest at PGP PIK Mall. Price has a greater influence than promotion, but both together contribute significantly to increasing buying interest. This finding indicates that an effective marketing strategy needs to consider aspects of competitive prices and attractive promotions to increase consumer purchasing decisions